The Use of Artificial Intelligence Technology in Enhancing Student Participation in Classroom Activities at the English Subject Teacher’s Association - Noor Eka Chandra; Nanik Mariani; Elsa Rosalina; Eka Puteri Elyani; Inayati Fitriyah Asrimawati; Muhammad Nuril Anwar; Youma Fairu Nazmi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
The development of various post-pandemic technologies has significantly changed teaching and learning activities. Through a brief interview between the head of the English Language Teachers’ Association in Banjar Regency and the head of the community service team, data was obtained that identified the issues faced by of the English Language Teachers’ Association members: 1) Teachers still lack information about various Artificial Intelligence (AI) technologies for English language teaching. 2) The teachers still lack information about free applications that can be used to support technology-based learning to increase student participation. Given the challenges faced by the partners, the goal of this community service was to provide secondary school teachers in South Kalimantan, especially in Banjar Regency, with insights into how AI plays a comprehensive role, as well as training in how to integrate various AI technologies to support the teaching and learning process. The implementation method offered for this activity included lectures, discussions, and collaborative learning with several stages, such as preparation, execution, and evaluation. The results of this training were as follows: 1) New experience for the teachers about AI-based support applications in the learning process. 2) How to integrate these applications into the classroom learning process. 3) Teachers successfully created their learning media using applications learned during the training. 4) Learning practices that integrated AI into the teaching process increased student motivation to learn English. The conclusion of this community service was that services could help the teacher in using technology, especially AI, to increase student participation in class.